Tydeid and triophtydeid mites (Acari: Tydeoidea) associated with grapevine (Vitaceae: Vitis spp.) in Brazil, with the descriptions of species of Prelorryia (André, 1980) and Tydeus Koch, 1835 - Da Silva, Guilherme Liberato; Da Cunha, Uemerson Silva; Rocha, Matheus Dos Santos; Panou, Eleni N.; Ferla, Noeli Juarez (Zootaxa, 2014)
We report on the Tydeidae and Triophtydeidae associated with grapevine (Vitis labrusca L. and Vitis vinifera L.) in Rio Grande do Sul State, Brazil, and describe a new species of Prelorryia, Prelorryia labrusca sp. nov., and two new species of Tydeus, Tydeus manoi sp. nov. and Tydeus riopardensis sp. nov. Brachytydeus formosa (Cooreman), B. podocarpa (Baker), Neolorryia pandana (Baker), Tydeus californicus (Banks), Pretydeus henriandrei Kaźmierski and Triophtydeus lebruni (André) are recorded and illustrated. A key to species of Tydeidae and Triophtydeidae from Brazil is provided.